A theoretical model for exciton binding energies in rectangular and parabolic spherical finite quantum dots - Taqi, A.; Diouri, J. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
. Using the variational method in real space and the effective-mass theory, we present quite an advanced semi-analytic approach susceptible for calculating the binding energy Eb of Wannier excitons in semiconductor quantum dot structures with rectangular and parabolic shapes of the confining potential in the so-called strong-confinement regime. Illustration is given for CdS, ZnSe, CdSe, GaAs structures of crystallites for both rectangular and parabolic quantum dots, and it displays a very good agreement between the experimental and theoretical results reported in literature.